Dynamic transcriptome and co-expression analysis suggest the potential roles of small secreted peptides from Tartary buckwheat (Fagopyrum tataricum) in low nitrogen stress response. (December 2021) - Liu, Changying; Xiang, Dabing; Wu, Qi; Ye, Xueling; Yan, Huiling; Zhao, Gang; Zou, Liang
Highlights: In total 932 putative small secreted peptides (SSPs) were firstly characterized in Tartary buckwheat (TB). 675 putative SSP genes were expressed in five tissues and 258 SSPs were tissue-specific expressed genes. 378 putative TB SSP genes showed diverse expression patterns in the roots under LN stress. Some established SSPs may regulate LN response of TB by modulating N transport and assimilation and IAA signaling. 53 LN-responsive receptor-like protein kinases were identified as the potential SSP receptors. Abstract: Small secreted peptides (SSPs) regulate nitrogen (N) response and signaling in plants. Although much progress has been made in understanding the functions of SSPs in N response, very little information is available regarding non-model plants. Tartary buckwheat ( Fagopyrum tataricum ), a dicotyledonous crop, has a good adaptability to low N (LN) stress; however, little is known regarding the associated mechanisms underlying this adaptation. In this study, 932 putative SSPs were genome-wide characterized in TB genome. Of these SSPs, 233 SSPs were annotated as established SSPs, such as CLE, RALF, PSK, and CEP peptides. The gene expression of 675 putative SSPs was detected in five tissues and 258 SSPs were tissue-specific expressed genes. To analyze the responses of TB SSPs to LN, the dynamic expression analysis of TB roots under LN stress was conducted by RNA-seq. The expression of 378 putative TB SSP genes was detected with diverse expression patterns under LN stress, and some important LN-responsive SSPs were identified. Co-expression analysis suggested SSPs may regulate the adaptability of TB under LN conditions by modulating the expression of the genes involved in N transport and assimilation and IAA signaling. Furthermore, 53 LN stress-responsive RLKs encoding genes were identified and they were predicted as potential SSP receptors. This study expands the repertoire of SSPs in plants and provides useful information for further investigation of the functions of Tartary buckwheat SSPs in LN stress responses.